Cactus to improve livestock feeding and income sources of the rural poor. Role of the FAO-Cactusnet [abstract] - Nefzaoui A. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Cactus (Opuntia ficus-indica, Cactaceae) is a xerophytic plant and an emergent crop, which evolved commercially during the second half of the XX century. The plant probably originated in Central Mexico, the region presenting the widest germplasm variability as well as the larger number of uses. The species of the Opuntia spp. subgenus have developed phenological, physiological and structural adaptations favourable to their development in arid environments, in which water is the main factor limiting the development of most plant species. Among these adaptations stand out its asynchronous reproduction, and its CAM metabolism, which combined with structural adaptations such as succulence, allow this plant to continue the assimilation of carbon dioxide during long periods of drought and in this way reach acceptable productivity levels even in years of severe drought. The physiological features conferring cactus pear drought tolerance, its adaptability and its utilization as human food and animal feed, as well as its suitability for the recovery of degraded lands of semiarid tropics, have raised global interest and driven the most recent trend of dispersal. Nowadays, the domesticated cactus is found in North America and South America, and many countries of Africa, Asia and Middle East. The establishment of sustainable production systems based on cactus may contribute to the food security of populations in agriculturally marginalized areas and to soil improvement. Cacti are some of the best plants for the reforestation of arid and semi-arid areas because they can resist scarce and erratic rainfall and high temperatures. Created in early 90s, today, the FAO International Technical Cooperation Network on Cactus (FAO-Cactusnet) includes more than 50 countries from all continents and aims actively to: (i) collect and disseminate information on production and planting, trade and markets, crop research, post harvest and processing and cochinilla on cactus pear; (ii) cooperate in the collection, conservation, exchange, evaluation and utilization of germplasm and monitor progress and usefulness of such exchanges; (iii) promote the ecological and social benefits of cactus pear; (iv) develop new food and carminic acid uses; and (v) exchange expertise and organise training courses, workshops and meetings of experts in order to improve technical capability of collaborating institutions. The network has regional representatives, country focal points, and scientific working groups that include, biology, fruit production, forage and rangelands, cochineal, plant genetic resources collection, conservation and evaluation, and agro industries and post harvest physiology. In addition, the Network is closely collaborating with FAO to disseminate and use cactus in new emerging countries through the development of technical cooperation projects.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)